Chalcophile-siderophile element systematics of hydrothermal pyrite from martian regolith breccia NWA 7533. (15th November 2018) - Lorand, J.-P.; Hewins, R.H.; Humayun, M.; Remusat, L.; Zanda, B.; La, C.; Pont, S.
Abstract: Unlike other martian meteorites studied so far, Martian regolith breccia NWA 7533 and paired meteorites that have sampled 4.4 Ga-old impact lithologies show only sulfides of hydrothermal origin (mostly pyrite (<1 vol.%) and scarce pyrrhotite). NWA 7533 pyrite has been analyzed for 25 chalcophile-siderophile trace elements with laser ablation-inductively coupled plasma mass spectrometer (LA-ICPMS). Micronuggets of highly siderophile elements-HSE (Os, Ir, Pt, Ru, Rh) along with occasional detection of Mo and Re were observed in half of the 52 analyzed crystals as random concentration spikes in time-resolved LA-ICPMS data. These nuggets are interpreted as variably altered remnants from repeated meteorite bombardment of the early martian crust, as are chondritic Ni/Co ratios of pyrite (10–20). Pyrite displays superchondritic S/Se (54, 000–3300) and Te/Se (0.3 to >1). The reasonably good positive correlation ( R 2  = 0.72) between Se and Ni reflects a temperature control on the solubility of both elements. Apart from the chalcogens S, Se and Te, pyrite appears to be a minor contributor (<20%) to the whole-rock budget for both HSE (including Ni and Co) and chalcophile metals Ag, As, Au, Cu, Hg, Pb, Sb, Tl and Zn. This deficit can result from (i) high (>400 °C) temperature crystallization for NWA 7533 pyrite, as deduced from its Se and Ni contents, (ii) magmatic sulfide-depletion of brecciated early martian crust, (iii) precipitation from near neutral H2 S-HS-H2 O-rich hydrothermal fluids that did not provide halogen ligands for extensive transport of chalcophile-siderophile metals. It is suggested that the 1.4 Ga lithification event that precipitated hydrothermal pyrite left the chalcophile-siderophile element budget of the early martian crust nearly unmodified, except for S, Se and Te.